1999
DOI: 10.1038/sj.ijo.0801026
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle UCP2 and UCP3 expression in trained and untrained male subjects

Abstract: OBJECTIVE:The new uncoupling proteins, UCP2 and UCP3, are thought to play a role in energy ef®ciency in humans. Endurance training has been suggested to have effects on resting metabolic rate and energy ef®ciency. We therefore determined UCP2 and UCP3 mRNA levels in skeletal muscle of trained and untrained male subjects. METHODS: Using reverse transcription-polymerase chain reaction (RT-PCR), expression of UCP2, UCP3L and UCP3S mRNA were measured in muscle biopsies from the quadriceps femoris in eight trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
79
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 24 publications
7
79
5
Order By: Relevance
“…25 The other muscle samples were quickly frozen and stored in liquid nitrogen for later UCP2, UCP3, b-actin and cytochrome b mRNA analysis. 16 Immediately prior to analysis, part of the latter sample was weighed, homogenised and then freeze -thawed twice. The homogenate was then centrifuged and the supernatant was analysed for citrate synthase (CS) activity using spectrophotometric detection.…”
Section: Slow Component Of V á O 2 Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The other muscle samples were quickly frozen and stored in liquid nitrogen for later UCP2, UCP3, b-actin and cytochrome b mRNA analysis. 16 Immediately prior to analysis, part of the latter sample was weighed, homogenised and then freeze -thawed twice. The homogenate was then centrifuged and the supernatant was analysed for citrate synthase (CS) activity using spectrophotometric detection.…”
Section: Slow Component Of V á O 2 Kineticsmentioning
confidence: 99%
“…13 Both uncouple mitochondrial oxidative phosphorylation, 14,15 which results in the production of heat without an increase in ATP production. Additionally, UCP3 mRNA has been inversely correlated with mechanical efficiency at low submaximal steady-state intensities 16 and found to be lower in endurance-trained rodents 17 and humans 16 compared to normal controls. The possibility, however, that both mitochondrial enzyme activity and UCP3 might have an adverse role in muscle efficiency of exercising healthy individuals during high intensity submaximal exercise has never been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Schrauwen et al. (29) reported that endurance-trained men had significantly reduced UCP3 mRNA levels in quadriceps muscles compared with untrained men and that UCP3 mRNA was negatively correlated with maximal oxygen uptake capacity in these subjects.Taken together, the results of these studies have led to the hypotheses that the "acute regulation of UCP3 gene expression has immediate and functionally important consequences" (37), whereas the decrease in UCP3 mRNA with long-term training results in an increase in the metabolic efficiency of muscle (6,30). These hypotheses imply that exercise results in major Address for reprint requests and other correspondence: J. O.…”
mentioning
confidence: 99%
“…Taken together, the results of these studies have led to the hypotheses that the "acute regulation of UCP3 gene expression has immediate and functionally important consequences" (37), whereas the decrease in UCP3 mRNA with long-term training results in an increase in the metabolic efficiency of muscle (6,30). These hypotheses imply that exercise results in major changes in mitochondrial composition, with a great short-term increase in UCP3 and a large long-term decrease in the amount of UCP3 relative to the other mitochondiral constituents.…”
mentioning
confidence: 99%
“…In humans, UCP3 mRNA (50,51) and protein levels (43) have been shown to be lower in endurance trained cyclists as compared to healthy control subjects. Additionally, we have recently observed that the UCP3 protein content is lower in all fiber types of endurance trained when compared to healthy individuals.…”
Section: Regulation Of Energy Expenditurementioning
confidence: 98%